Skrinning Fitokimia, Kandungan Flavonoid Total dan Uji Aktivitas Antioksidan Ekstrak Kayu Balakka (Phyllanthus emblica L.) - Adam, Dini Hariyati (Departemen Kimia Universitas Andalas, 2024)
Balakka plant (Phyllanthus emblica L.) is a plant that has the potential to protect the pancreas, through antioxidant and anti-diabetic activities. This study aims to determine the content of metabolite compounds of balakka wood samples macerated using hexane, ethyl acetate and ethanol solvents, total flavonoid content and antioxidant activity of balakka wood extract. Total flavonoid content was determined using AlCl3 and kursetin standard solution. This AlCl3 method will later produce a red chelate that can be measured with a visible spectrophotometer at a wavelength of 435 nm. While antioxidant activity was measured by the DPPH method. The results showed that the highest total flavonoid content was in the ethanol extract of 60.39 mg/L and antioxidant activity with an IC50 value of 28.97 ppm. Thus, the ethanol extract of balakka wood showed the highest flavonoid content and can be categorized as a very strong antioxidant.